Sustaining Latin America's Resurgence : Some Historical Perspectives - Singh, Anoop (IMF Working Papers; Working Paper, 2006)
This paper looks at the historical lessons that might serve to entrech Latin America's newly resurgent growth phase. It briefly reviews the post-World War II experiences in Latin America and Asia, focusing on the conditions that favored capital accumulation and productivity growth in the faster growing economies. Among these, the paper highlights the importance of stable macroeconomic policies, especially fiscal policy.